"De pobre huerfanita a viuda negra": la agencia de la mujer en las Tristanas de Pérez Galdós y Buñuel - Otero Luque, Frank (Studium, 2018)
Las diferencias más obvias entre la novela de Pérez Galdós y el filme de Buñuel son el lugar el tiempo en que están ambientadas las obras: en Madrid alrededor de 1880, y en Toledo por el año de 1929. No tan obvio es el hecho de que sus respectivos autores pertenecen a generaciones diferentes: el primero, a la llamada Generación de 1868; y el segundo a la Generación de 1927. Por tal motivo Galdós y Buñuel tienen ópticas distintas acerca de la mujer y de la causa feminista (avant la lettre en el caso del primero). Más aún, mientras que el escritor isleño era un cultor del realismo literario, defensor de la burguesía y liberal; el cineasta aragonés era surrealista, antiburgués y republicano. Estas diferencias hacen que la comparación entre la obra literaria y la cinematográfica sea particularmente interesante. The transformation of a poor, orphaned little girl into a merciless black widow: woman’s agency in Pérez Galdós’ and Buñuel’s respective Tristanas Abstract The space and time settings are the most obvious difference between Pérez Galdós’ novel and Buñuel’s film: Madrid around 1880, and Toledo near 1929, respectively. Not as obvious is the fact that these authors do not belong to the same generation: Pérez Galdós to the so-called 1868 Generation, and Buñuel to the 1927 Generation. Because of this reason, Pérez Galdós and Buñuel have different views of women and the feminist cause (avant la lettre in the case of the former). Furthermore, the Canarian was a liberal bourgeois writer, representative of the literary realism, while the Aragonese was surrealist, anti-bourgeois and Republican filmmaker. All these differences make the comparison between the literary and the cinematographic art pieces particularly interesting.